The effect of running versus cycling high-intensity intermittent exercise on local tissue oxygenation and perceived enjoyment in 18–30-year-old sedentary men - Kriel,Yuri; Askew,Christopher D.; Solomon,Colin (PeerJ, 2018)
Background High-intensity interval training (HIIT) has been proposed as a time-efficient exercise format to improve exercise adherence, thereby targeting the chronic disease burden associated with sedentary behaviour. Exercise mode (cycling, running), if self-selected, will likely affect the physiological and enjoyment responses to HIIT in sedentary individuals. Differences in physiological and enjoyment responses, associated with the mode of exercise, could potentially influence the uptake and continued adherence to HIIT. It was hypothesised that in young sedentary men, local and systemic oxygen utilisation and enjoyment would be higher during a session of running HIIT, compared to a session of cycling HIIT. Methods A total of 12 sedentary men (mean ± SD; age 24 ± 3 years) completed three exercise sessions: a maximal incremental exercise test on a treadmill (MAX) followed by two experiment conditions, (1) free-paced cycling HIIT on a bicycle ergometer (HIITCYC) and (2) constant-paced running HIIT on a treadmill ergometer (HIITRUN). Deoxygenated haemoglobin (HHb) in the gastrocnemius (GN), the left vastus lateralis (LVL) and the right vastus lateralis (RVL) muscles, oxygen consumption (VO2), heart rate (HR), ratings of perceived exertion (RPE) and physical activity enjoyment (PACES) were measured during HIITCYC and HIITRUN. Results There was a higher HHb in the LVL (p = 0.001) and RVL (p = 0.002) sites and a higher VO2 (p = 0.017) and HR (p < 0.001) during HIITCYC, compared to HIITRUN. RPE was higher (p < 0.001) and PACES lower (p = 0.032) during HIITCYC compared to HIITRUN. Discussion In sedentary individuals, free-paced cycling HIIT produces higher levels of physiological stress when compared to constant-paced running HIIT. Participants perceived running HIIT to be more enjoyable than cycling HIIT. These findings have implications for selection of mode of HIIT for physical stress, exercise enjoyment and compliance.
Keywords: HIIT; NIRS; Sedentary; Enjoyment; Exercise mode